Sustainability principles and practice - Robertson, Margaret (Routledge, 2017)
This new and expanded edition builds upon the first edition’s accessible and comprehensive overview of the interdisciplinary field of sustainability. The focus is on furnishing solutions and equipping the student with both conceptual understanding and technical skills for the workplace.